2012
DOI: 10.1021/es301977w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Charge on the Uptake and Distribution of Gold Nanoparticles in Four Plant Species

Abstract: Small (6-10 nm) functionalized gold nanoparticles (AuNPs) featuring different, well-defined surface charges were used to probe the uptake and distribution of nanomaterials in terrestrial plants, including rice, radish, pumpkin, and perennial ryegrass. Exposure of the AuNPs to plant seedlings under hydroponic conditions for a 5-day period was investigated. Results from these studies indicate that AuNP uptake and distribution depend on both nanoparticle surface charge and plant species. The experiments show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
220
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(248 citation statements)
references
References 53 publications
22
220
0
6
Order By: Relevance
“…Plant species can differ in their physiology, and such differences result in variations regarding uptake of nanoparticles, as reported for example by Cifuentes et al (2010), Larue et al (2012), and Zhu et al (2012). These works showed how crops species belonging to different botanical families, and exposed to either magnetic carbon-coated, titanium dioxide or gold nanoparticles respectively, presented diverse absorption and accumulation patterns inside the plants.…”
Section: Plant Absorption and Uptake Of Nanoparticlesmentioning
confidence: 75%
See 2 more Smart Citations
“…Plant species can differ in their physiology, and such differences result in variations regarding uptake of nanoparticles, as reported for example by Cifuentes et al (2010), Larue et al (2012), and Zhu et al (2012). These works showed how crops species belonging to different botanical families, and exposed to either magnetic carbon-coated, titanium dioxide or gold nanoparticles respectively, presented diverse absorption and accumulation patterns inside the plants.…”
Section: Plant Absorption and Uptake Of Nanoparticlesmentioning
confidence: 75%
“…Cifuentes et al (2010) reported higher accumulation of carbon-coated iron nanoparticles in the roots of pea compared with sunflower and wheat, and faster translocation to the aerial parts in pea and wheat compared with sunflower and tomato. On the other hand, Zhu et al (2012) found that radish and ryegrass roots accumulated higher amounts of gold nanoparticles than rice and pumpkin, and that positively charged gold nanoparticles were taken up faster by the roots than negatively charged one, whereas these last ones were more efficiently translocated to the aerial parts. This phenomenon was explained by the negative charge present in the plant cell walls, favoring accumulation of positively charged nanoparticles in the tissues, and hampering its movement through the plant.…”
Section: Movement Of Nanoparticles Inside Plantsmentioning
confidence: 94%
See 1 more Smart Citation
“…The surface charge can be a significant factor in the plant nanotoxicity studies. Zhu et al (2012) concluded that small sized positively charged Au NPs were usually confined to the roots of terrestrial plants, whereas the negatively charged NPs were easily translocated to shoots and leaves. The fate of ENMs is also affected by surface coating (Buzea et al, 2007;Unrine et al, 2012).…”
Section: Physiochemical Properties Of Enmsmentioning
confidence: 99%
“…It is unknown whether these exchange sites might also facilitate transport of MNMs. Recently, the importance of surface charge to plant uptake of 6-10 Au MNMs in rice, radish, pumpkin, and perennial ryegrass was examined (Zhu et al, 2012). Positively charged particles were taken up into the roots more readily, whereas negatively charged MNMs were translocated into the plant shoots in higher concentrations.…”
Section: Importance Of Mnm Intrinsic Properties On Root Uptakementioning
confidence: 99%